A fault model extension for a geometric fault isolation methodology to detect leakages and sensor faults on engine test beds. (March 2022) - Wohlthan, Michael; Schadler, Doris; Pirker, Gerhard; Wimmer, Andreas
Abstract: Analytical model-based methods for fault diagnosis on engine test bench systems remain the subject of intensive research. In some cases, such methods are also being used productively even though their application is mainly limited to the isolation of sensor faults. This paper presents a method for isolating process faults—and leakages in particular—that does not require any direct changes to the analytical models used for residual generation. Based on a geometric isolator, this method generates relations between fault causes and fault symptoms through the definition of fault models using latent variables. The application of the methodology is first explained in detail using a simple example. Taking data from a simulated engine test bench, we then show how different causes of faults, including sensor faults and leakages at different positions, can be correctly isolated.